Extração de catarata pela técnica de facoemulsificação e implante de lente intra-ocular de câmara posterior em pacientes com uveíte - Yamane, Cláudio de Lima (2004)
This study reports outcomes of phacoemulsification cataract extraction and posterior chamber intraocular lens implantation within the capsular bag in patients with uveitis. We retrospectively reviewed the charts of 189 patients (242 eyes) with uveitis who underwent phacoemulsification cataract extraction at the Uveitis and Ocular Imunology Unit from the McGill University Health Centre. Average follow-up was 46 ± 31,2 months. Average preoperative visual acuity was 20/100 and average postoperative visual acuity was 20/40. Hundred and forty-six eyes (59,9%) attained visual acuity better than 20/40. Visual loss ocurred in 26 eyes. The most common peroperative complication was posterior capsule rupture with vitreous loss seen in 7 eyes (3%). Recurrence of uveitis was the most common postoperative complication seen in 73 eyes (30,16%). Other postoperative complication included iris atrophy (28,51%), ocular hypertension (28,09%), epirretinal membrane (26,44%), posterior capsule opacification (198,00%), cystoid macular edema (13,63%), ocular hypotony (12,80%), optic disc atrophy (8,67%) and posterior synechie (6,61%). We concluded that phacoemulsification cataract extraction with posterior chamber lens implantation is safe in patients with uveitis. Successful visual results are observed in long-term follow-up despite the prevalence of recorrence of uveitis, posterior capsule opacification and macular abnormalities.